Dynamic Behavior of Articulated Vehicle with Indirect Connection of Adjacent Sections (Current Problems in Rail Vehicles, 2021)
In this article are described partial results of analysis of the dynamic behaviour of two-section coach with common 3-axle bogie. The analysis is focused on running stability at higher speeds, compatibility with bridges, lateral dynamics in curve transition and forces caused in wheel–rail contact.
Keywords: D-DART; common 3-axle bogie; indirect articulation; dynamic behaviour; running stability; comfort in curve transition; bridge compatibility